JOB BURNOUT DAN REDUCED AUDIT QUALITY PRACTICES (RAQP) DALAM PERSPEKTIF ROLE STRESS - Richard Wiratama; Suwandi Ng; Lukman Lukman (SIMAK, 2019)
The purpose of this study were to investigate the influence of role stressors (role ambiguity, role conflict, and role overload) to the reduced audit quality practices (RAQP) were tested both directly and indirectly through the variable job burnout. Respondents in this study are auditors who working in 15 Public Accounting Firms at Sulawesi, Papua, and Maluku. Data collection procedures in the study were taken directly (Administered Personality Questionnaires) in Public Accounting Firm located in Makassar, while the public accounting firm which the outside of Makassar were spread by sending questionnaires (Mail Questionnaires). Data were analyzed using the path analysis. The results of this study indicate that role stressors (role ambiguity, role conflict, and role overload) have a positive and significant effect on job burnout and also job burnout has a positive and significant effect on reduced audit quality practices (RAQP). The direct influence of role stressors (role ambiguity, role conflict, and role overload) have a positive but not high enough to have a strong influence on reduced audit quality practices (RAQP). Implications practice of this research are as learning profession Public Accountants and auditors to take preventive actions and improvements on stress due to role stressors.